2020
DOI: 10.48550/arxiv.2008.11147
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Tale of Two Cities: Software Developers Working from Home During the COVID-19 Pandemic

Denae Ford,
Margaret-Anne Storey,
Thomas Zimmermann
et al.

Abstract: The COVID-19 pandemic has shaken the world to its core and has provoked an overnight exodus of developers that normally worked in an office setting to working from home. The magnitude of this shift and the factors that have accompanied this new unplanned work setting go beyond what the software engineering community has previously understood to be remote work. To find out how developers and their productivity were affected, we distributed two surveys (with 3,634 responses)-weeks apart to understand the presenc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 28 publications
2
26
0
Order By: Relevance
“…2) Challenges and Growth: Prior studies on professional developers identified several challenges stemming from working from home during the pandemic, such as a poor work environment, poor work-life balance, and difficulties in collaborating [8], [10]. While these issues were also present in the student team, they were reported to a less significant degree.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…2) Challenges and Growth: Prior studies on professional developers identified several challenges stemming from working from home during the pandemic, such as a poor work environment, poor work-life balance, and difficulties in collaborating [8], [10]. While these issues were also present in the student team, they were reported to a less significant degree.…”
Section: Discussionmentioning
confidence: 99%
“…While these issues were also present in the student team, they were reported to a less significant degree. We also observed that the students had to balance their academic commitments, similar to professional developers balancing external commitments such as family [2], [8]. Students who participate in such projects may be more adept at handling multiple responsibilities when entering the professional environment, which is supported by increased confidence in their task prioritization abilities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations